Estimating yield of food crops grown by smallholder farmers: A review in the Uganda context - Fermont, Anneke; Benson, Todd (International Food Policy Research Institute, 2011)
Precise agricultural statistics are essential for planning and evaluation of agricultural investments to improve the productivity and profitability of smallholder farming systems. However, accurately estimating crop yields is never easy and is even more of a challenge in the context of African farming systems that are characterized by smallholder farms that produce a wide range of diverse crops. With specific reference to yield estimation for food crops under smallholder farming conditions in Uganda, this paper evaluates the various methods that are available to estimate crop production and cropped area in such farming systems. A description and summary tables from a database of estimated crop yields in Uganda that was collated from a large set of field studies over past decades are also provided.